2000
DOI: 10.1074/jbc.275.10.7343
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of c-myc Transcription by Interleukin-2 (IL-2)

Abstract: Regulation of c-myc expression is known to occur at the level of transcription initiation. However, the participating promoter elements and their cognate binding proteins have not been fully characterized. c-myc transcription can be stimulated by a number of cytokines including interleukin-2 (IL-2). We have identified a novel IL-2-responsive element, located in the 5-flanking region of the c-myc gene, between nucleotides ؊1406 and ؊1387 (relative to the P2 promoter). This element belongs to the family of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Together with the fact that binding of endogenous c‐Myc to the distal promoter element is significantly enhanced upon IL‐15 stimulation in peripheral blood NK cells and correlates with an increase in KIR transcription, this provides a direct link between NK cell activation signals and KIR expression required for acquisition of the effector function during NK cell education . In addition, it has been demonstrated that stimulation with IL‐2, an important regulator of NK cell activity, increases c‐myc expression in natural killer cell line NK3.3 . However, c‐myc expression in NK cells in cancer patients has never been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the fact that binding of endogenous c‐Myc to the distal promoter element is significantly enhanced upon IL‐15 stimulation in peripheral blood NK cells and correlates with an increase in KIR transcription, this provides a direct link between NK cell activation signals and KIR expression required for acquisition of the effector function during NK cell education . In addition, it has been demonstrated that stimulation with IL‐2, an important regulator of NK cell activity, increases c‐myc expression in natural killer cell line NK3.3 . However, c‐myc expression in NK cells in cancer patients has never been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…These observations raise the possibility that regulation of c - Myc expression by STAT5 might be likewise unconventional, possibly involving distal elements. In support of this proposition, we previously attempted and failed to detect STAT5 binding along the c - Myc gene [ 13 ], including at GAS elements present in its promoter and known to mediate transcriptional response to other STAT family members [ 39 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…c-Myc plays a role in hematopoietic homeostasis, and its upregulation is essential for initiating the differentiation of HSPCs [53]. Expression of c-Myc can be upregulated by IL-2 [54]. Both c-Myc and RSK1-p90 are downstream targets of ERK1/2 [55,56].…”
Section: Discussionmentioning
confidence: 99%